Review Artikel: Evaluasi Efektivitas Berbagai Macam Metode Sterilisasi - Herta Meidya Nurhalita; Alfi Dwi Seviah; Kurrota Ayyun; Laila Sabila Sindriyani; Yeka Khafidz Ila Rosyidah; Dewi Rahmawati; Dzakiah Zhirotul Wida; Fitrul Mubarok (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Sterilization is a process that aims to remove all forms of microbial life, including bacteria, viruses, fungi, and spores, from an object or surface. This process is very important in various fields, such as medicine, laboratories, food industry, and pharmaceuticals, to prevent infection and contamination. This article was written through a literature review of articles originating from international and national journals. Data searches were carried out through scientific-based websites and databases, namely Google Scholar, Science Direct, and PubMed. The results show that of various sterilization methods such as autoclave, oven, ozone, filtration, steam, 70% alcohol, UV radiation and gamma rays, each has different effectiveness in killing microorganisms, and each method has advantages and disadvantages. . The conclusion of this article provides a comprehensive evaluation of the effectiveness of various sterilization methods used in laboratory and industrial contexts. Various techniques, such as autoclave, oven, ozone, filtration, steam, 70% alcohol, UV radiation and gamma rays.